EFEKTIFITAS LAYANAN KONSELING KELOMPOK DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI IPS 1 SMA NEGERI 3 JEMBER TAHUN AJARAN 2014/2015 - Titin Swastinah (FKIP Universitas Islam Jember, 2015)
This study employed guidance and counseling action research (PTBK) that involved repeated cycles consisting of planning, acting, observing, and reflecting as proposed by Kemmis, S. and McTaggert, R. (1988). This study was aimed at investigating whether or not the group guidance and counseling is effective to develop the students’ motivation at class XI IPS 1, SMA Negeri 3 Jember. On the basis of research findings, this strategy could highly motivate the students of class XI IPS 1, SMA Negeri 3 Jember, to learn. Based on the research findings, it is highly suggested that the guidance and counseling (BK) teacher who have similar problems implement this strategy as one of alternatives to motivate their students.Keywords: Students’ motivation, group guidance and counseling.